Taxation and Unemployment - Zee, Howell (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews conceptual linkages between taxation and unemployment, available empirical evidence and country policies that may have a bearing on these linkages in the OECD and in a sample of developing and transitional economies, Fund policy advice on these issues, and tax policy options in addressing the unemployment problem. It concludes that the emphasis in policy should be placed on minimizing tax distortions, rather than on formulating activist tax policies to reduce unemployment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet